Effective strategy implementation conceptualizing firms? strategy implementation capabilities and assessing their impact on firm performance - Huber, Adele J.; SpringerLink (Online service). (Wiesbaden Gabler, 2011)
Adele J. Huber discovers that a firm's strategy implementation capabilities are a key driver of the strategies' performance outcomes. Drawing on organizational learning theory, she identifies the organizational abilities and processes that constitute a firm's Strategy Implementation Capability construct and shows empirically that the concept is very valuable in explaining how innovative strategies translate into a firm's performance. Her findings are particularly interesting for managers and researchers who focus on strategy formulation and execution. They also show the relation between strategy implementation and competitive advantage.
Conceptualization of firms' implementation capabilities based on organizational learning theory; Scale development and validation of the Strategy Implementation Capability construct; Empirical analyses regarding the construct's effects on firm performance based on data from senior manager dyads; Implications for management and research
Electronic reproduction.
Keywords: Strategic planning; Electronic books